Membangun Etika Pengelolaan Melalui Paradigma Baru Manajemen Pendidikan Islam - Hosen, Hosen; Nasrullah, Nasrullah (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2024)
This article explores the paradigm of management development in Islamic education, including its scope, application, core principles, and the importance of ethical foundations in sustainable educational leadership. The study delves into key aspects such as the conceptual framework of Islamic education management, the necessity of collaborative efforts, and the relevance of applying Islamic values in organizational governance. Within the spectrum of Islamic educational thought, management holds a central role as it is closely linked to the control and direction of social institutions. Foundational values such as equality, justice, and the fulfillment of rights and responsibilities serve as the ethical backbone of management practices. To construct a system that balances freedom and accountability, an in-depth understanding of the Islamic principle of equality is essential. In practice, these values must be dynamically interpreted and applied in response to environmental changes and societal developments. The study emphasizes a management model aimed at public welfare and grounded in strong ethical commitment. It also serves as a moral and spiritual reminder for Muslim leaders and managers to perform their duties in alignment with Islamic ethics. When applied in daily managerial practices, these principles enable individuals and institutions to achieve balanced success, contribute meaningfully to society, and remain faithful to the ethical calls of Islam. This study adopts a qualitative approach, with data gathered from various secondary sources such as articles, books, internet references, and other relevant literature. The data were then analyzed thematically to produce insights aligned with the research objectives.